Enacting Plant-Inspired Robotics - Lee, Jonny; Calvo, Paco (Frontiers in Neurorobotics, 2022)
Plants offer a source of bioinspiration for soft robotics. Nevertheless, a gap remains in designing robots based on the fundamental principles of plant intelligence, rooted in a non-centralised, modular architecture and a highly plastic phenotype. We contend that a holistic approach to plant bioinspiration—one that draws more fully on the features of plant intelligence and behaviour—evidences the value of an enactivist perspective. This is because enactivism emphasises not only features of embodiment such as material composition and morphology but also autonomy as an important aspect of plant intelligence and behaviour. The enactivist sense of autonomy concerns the dynamics of self-producing systems (such as plants) that create a distinction between themselves and a domain of interactions that bear on the system’s conditions of viability. This contrasts with the widespread but diluted notion of autonomy that merely indicates the independent operability of a system for an arbitrary period. Different notions of autonomy are relevant for soft roboticists, for instance, when evaluating limitations on existing growing robots (‘growbots’) that take bioinspiration from plants but depend on a fixed source of energy and material provided by an external agent. More generally, plant-inspired robots serve as a case study for an enactivist approach to intelligence whilst, correspondingly, enactivism calls attention to the possibility of non-zoological forms of intelligence embodied in a self-organising, autonomous system.